Temporal Associations Between Moral Injury and Posttraumatic Stress Disorder Symptom Clusters in Military Veterans. Issue 3 (4th February 2019) - Currier, Joseph M.; McDermott, Ryon C.; Farnsworth, Jacob K.; Borges, Lauren M.
Abstract: War zone veterans who experience posttraumatic stress disorder (PTSD) symptoms might struggle with co‐occurring cognitive, emotional, and behavioral expressions of suffering that align with conceptual definitions of moral injury (MI). However, given that PTSD is a multidimensional condition, disentangling the apparent interplay with MI may inform clinical practice and research. This study incorporated a cross‐lagged design to explore temporal associations between self‐ and other‐directed outcomes related to MI and severity of DSM‐5 PTSD symptom clusters while accounting for depressive symptoms. Drawing on the Expressions of Moral Injury Scale–Military Version in a community sample of 182 previously deployed veterans, MI‐related outcomes were linked with severity of PTSD symptom clusters at two assessments spaced apart by 6 months, r s = .58–.62. Of possible models for conceptualizing the temporal nature of these associations, structural equation modeling analyses revealed a cross‐lagged primary MI model best fit veterans' responses. Within this model, veterans' self‐directed MI at Time 1 predicted greater PTSD symptoms at the 6‐month follow‐up. However, an equivalent cross‐lagged path also emerged between Time 1 PTSD Cluster D symptoms and self‐directed MI at Time 2, suggesting the value of a reciprocal MI model for this symptom domain. In contrast, other‐directed outcomes of MI were not linked with PTSD in the presence of other variables. Overall, these findings support the prognostic value of assessing for MI‐related outcomes among veterans who might be struggling with PTSD symptomatology, particularly with respect to self‐directed problems associated with enduring moral distress. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Asociaciones temporales entre daño moral y grupos sintomáticos de TEPT en veteranos militares ASOCIACIONES TEMPORALES ENTRE DAÑO MORAL Y TEPT Los veteranos en zona de guerra que experimentan síntomas de trastorno de Estrés Postraumático (TEPT) pueden tener dificultades con las expresiones de sufrimiento cognitivas, emocionales y conductuales concomitantes que se alinean con las definiciones conceptuales de daño moral (DM). Sin embargo, dado que el TEPT es una condición multidimensional, desenredar la interacción aparente con el DM puede informar la práctica clínica y la investigación. Este estudio incorporo un diseño cruzado para explorar las asociaciones temporales entre los resultados auto‐dirigidos y dirigidos por otros relacionados con el DM y la gravedad de los grupos sintomáticos de TEPT del DSM‐5 mientras se toman en consideración los síntomas depresivos. Basándose en las Escala de Expresiones de Daño Moral ‐ Versión Militar en una muestra comunitaria de 182 veteranos previamente desplazados, los resultados relacionados con DM estuvieron ligados con la severidad de los grupos sintomáticos de TEPT en las dos evaluaciones, espaciadas por 6 meses, rs = .58 ‐.62. De los posibles modelos para conceptualizar la naturaleza temporal de estas asociaciones, el análisis de modelos de ecuaciones estructurales revelo que un modelo de DM primario cruzado se adapta mejor a las respuestas de los veteranos. Dentro de este modelo, los veteranos con DM auto‐dirigido en el momento 1 predijeron más síntomas de TEPT a los 6 meses de seguimiento. Sin embargo, tambien surgió un camino cruzado equivalente entre el tiempo 1 del grupo sintomático D de TEPT y DM auto‐dirigido en el tiempo 2, sugiriendo el valor de un modelo de DM recíproco para este dominio de síntomas. En contraste, los resultados de DM dirigido a otros no estuvieron ligados con TEPT en la presencia de otras variables. En general, estos hallazgos apoyan el valor pronóstico de la evaluación de los resultados relacionados con DM entre veteranos que podrían estar luchando con sintomatología de TEPT, particularmente con respecto a los problemas auto‐dirigidos asociados con sufrimiento moral duradero. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Temporal Associations Between Moral Injury and PTSD Symptom Clusters in Military Veterans Traditional Chinese 標題: 退役軍人當中道德創傷跟PTSD症狀聚類的時序關連 撮要: 曾於戰區服役並有創傷後壓力症(PTSD)症狀的退役軍人, 可能同時面對反映痛苦的認知、情緒與行為, 而那跟道德創傷概念的定義吻合(MI)。可是, PTSD的情況具多面向, 若可釐清其於MI的相互作用, 可能有助臨床治療和研究。本研究採用交叉延宕設計, 對抑鬱症狀作解釋, 並探索因個人或他人引致與MI相關的症狀跟DSM‐5 PTSD症狀聚類嚴重度之間的時序關連。社區樣本由182名退役軍人組成。我們透過樣本於道德創傷量表軍人版的評估表現, 發現在兩次相隔6個月的評估中, MI相關的症狀跟PTSD症狀聚類嚴重度有關(rs = .58–.62)。在多個有可能把以上時序關連概念化的模型中, 結構性方程模型分析反映, 一個初級的交叉延宕MI模型與退役軍人的表現最為吻合。在此模型中, 退役軍人於時點1自我引致的MI, 預測了在6個月後跟進期時有較嚴重的PTSD症狀。可是, 在時點1的PTSD症狀聚類D跟時點2自我引致的MI之間, 展現了同等的交叉延宕路徑, 反映我們值得探討這症狀範疇中具相互作用的MI模型。相反, 在其他變量存在下, 他人引致的MI症狀跟PTSD無關。總括來說, 對於受PTSD症狀學所困擾的退役軍人, 尤其是因承受道德悲痛而產生自我引致症狀的人, 本研究結果反映, 評估其MI相關症狀有預測價值。 Simplified Chinese 标题: 退役军人当中道德创伤跟PTSD症状聚类的时序关连 撮要: 曾于战区服役并有创伤后压力症(PTSD)症状的退役军人, 可能同时面对反映痛苦的认知、情绪与行为, 而那跟道德创伤概念的定义吻合(MI)。可是, PTSD的情况具多面向, 若可厘清其于MI的相互作用, 可能有助临床治疗和研究。本研究采用交叉延宕设计, 对抑郁症状作解释, 并探索因个人或他人引致与MI相关的症状跟DSM‐5 PTSD症状聚类严重度之间的时序关连。小区样本由182名退役军人组成。我们透过样本于道德创伤量表军人版的评估表现, 发现在两次相隔6个月的评估中, MI相关的症状跟PTSD症状聚类严重度有关(rs = .58–.62)。在多个有可能把以上时序关连概念化的模型中, 结构性方程模型分析反映, 一个初级的交叉延宕MI模型与退役军人的表现最为吻合。在此模型中, 退役军人于时点1自我引致的MI, 预测了在6个月后跟进期时有较严重的PTSD症状。可是, 在时点1的PTSD症状聚类D跟时点2自我引致的MI之间, 展现了同等的交叉延宕路径, 反映我们值得探讨这症状范畴中具相互作用的MI模型。相反, 在其他变量存在下, 他人引致的MI症状跟PTSD无关。总括来说, 对于受PTSD症状学所困扰的退役军人, 尤其是因承受道德悲痛而产生自我引致症状的人, 本研究结果反映, 评估其MI相关症状有预测价值。